Linguistic Realization of the Concept “House/Home” in Yu.V. Trifonov’s Discourse (Proceedings of Southern Federal University. Philology, 2018)
Dinara R. Valeeva (Kazanˊ Russian Federation, Tatarstan)The increased attention of modern linguistic science to the questions of conceptualization of the surrounding world is due to the fact that V. von Humboldt’s ideas about the interrelation between the language and the character of the people are being actualized, therefore many studies investigate language and its units in system paying respect to the “human factor”.In connection with this, the number of works devoted to the study of the concept is increasing, because the concept, being the main form of the categorization of knowledge and the main means of conceptualizing of reality, occupies an important position in individual and collective linguistic consciousness. By the totality of concepts, one can judge the mental model of reality reflected in the language in general and in the consciousness of certain native speakers in particular. Author considers that the concept is a dynamic mental structure mediating between man and the world, combining conceptual, value and cultural information realized in the verbal units of a certain language.The given article is devoted to the study of the linguocultural concept “House / Home” in the Russian world picture on the example of works by contemporary writer Y.V. Trifonov. The study showed that in Trifonov’s discourse the concept “House / Home”, on the one hand, coincides with the general language concept - cozy, bright, it is the link between family members and the source of soul forces for a person. On the other hand, such a house, as a rule, existed only in the past, and it often acts as an analogue of the homeless, becoming an “antihouse/home”. The core of the concept “House / Home” in Y. Trifonov’s texts includes not only the standard cognitive signs “construction”, “family”, “economy”, but also the “exchange” and “apartment issue” sеmes, forming an individual author’s picture of the world. Also the author came to conclusion that the seme “exchange” of the common language concept “House / Home”, can be attributed to the peripheral part of the content, and “apartment issue” to the near-nuclear zone, because nowadays the idea about apartment house for Russians is dominant. At the same time, in Y. Trifonov’s texts the word “apartment” is the key representative of the concept “House / Home” in comparison the words “house” and “home”.Key words: concept, house, home, Trifonov, opposition, lexem, seme, verbalization, discourse, conceptual character (attribute), representative.DOI 10.23683/1995-0640-2018-1-184-190